Mechanism for strengthening the integrity of device carrying-in/out record management applying blockchain - et.al, Jinsu Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the case of a general goods carry-in/out management system, each device is registered by assigning a unique number to RFID, and is managed as data from a server. In this method, a single server is used, and integrity corruption behavior may occur due to errors of the single server or external attacks. Blockchain uses a peer-to-peer (P2P) network to strengthen data integrity through consensus between each client. In addition, since it does not rely on a single server, the availability of a single system can be improved in that the error of a single system does not significantly affect the entire network. In order to prevent damage to the integrity of the system, we propose a mechanism to strengthen integrity through blockchain